Effect of laser pulse capacity (titanium-blue sapphire) on propagation properties in photonic crystal fibers - Marwan Younis; Abdul Ghafoor Abdullah (College of Education for Pure Sciences, 2012)
Abstract: Two designs of photonic crystal fibers with similar parameters are proposed, the difference only in the air fraction. The Air fraction of the PCF1 is 0.4, while for the second design is increased to 0.45. The propagation properties of the both designs are investigated. The results show that the zero dispersion wavelength (λZD) for PCF1 and PCF2 are pushed to the visible region far away from the 1.27µm as in traditional silica fibers. The effect of the laser pulsed power of the (Ti-Sapphire) of 0.8µm on the dispersion profile of PCF1 and PCF2 is also studied. The λZD for the PCF1 is blue shifted, while a small increment in the air fraction as in PCF2 cause red shift for λZD. On the other hand, the sensitivity of the PCF2 for the pulse power (0.3nm/kW) is 10 times more comparing with the sensitivity (0.03nm/kW) of the PCF1.